Development of Augmented Reality Media for Local Wisdom Learning - Sapta, Andy; Risnawati, Erna; Panjaitan, Dedy Juliandri; Marisa, -; Nisa, Uliya Khoirun (Society of Visual Informatics, 2025)
Indonesia, as an archipelago, has much local wisdom. Teaching local wisdom materials in Indonesia so far tends to use images or videos that are not interactive. This medium has limitations in terms of student involvement. Therefore, it is necessary to develop learning media that can effectively display local wisdom from various cultures. This research uses the Research and Development method to develop Augmented Reality applications. Augmented Reality Local Wisdom: This research developed local wisdom in Indonesia, including the Batak, Javanese, Sundanese, and Betawi tribes. Material culture encompasses traditional clothing, vernacular architecture, indigenous weapons, and regional motifs. The research population comes from the provinces of North Sumatra, Jakarta, West Java, and Yogyakarta. This study's research product involves developing a project-based learning model grounded in local wisdom and supported by Augmented Reality. The development results show that using Augmented Reality in learning, particularly through the project-based learning model, is beneficial because it helps students describe material culture more effectively. This study suggests that students can become more engaged and interactive in their learning. Additionally, using Augmented Reality, students can explore culture more contextually, enhance their problem-solving skills, and reduce the time and costs associated with learning about local culture. The use of AR in local wisdom-based learning could be an innovative solution to enhance the quality of education and cultural preservation in the digital age.